2017
DOI: 10.1242/jeb.162701
|View full text |Cite
|
Sign up to set email alerts
|

Expression and light-dependent translocation of β-arrestin in the visual system of the terrestrial slug Limax valentianus

Abstract: Vertebrates, cephalopods and arthropods are equipped with eyes that have the highest spatiotemporal resolution among the animal phyla. In parallel, only animals in these three phyla have visual arrestin specialized for the termination of visual signaling triggered by opsin, in addition to ubiquitously expressed β-arrestin that serves in terminating general G protein-coupled receptor signaling. Indeed, visual arrestin in and rodents translocates to the opsin-rich subcellular region in response to light to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…2A), but they escaped only from short wavelength light if the irradiance was low (10 μW cm −2 ; Fig. 2B), consistent with the higher sensitivity of the slugs' eyes to short-wavelength light (Suzuki et al, 1979;Matsuo et al, 2017Matsuo et al, , 2019. We judged the avoidance behaviour based on whether more than half of the slug's body was within the dark compartment (criterion number 1).…”
Section: Wavelength Dependency Of Avoidance Behavioursupporting
confidence: 54%
See 2 more Smart Citations
“…2A), but they escaped only from short wavelength light if the irradiance was low (10 μW cm −2 ; Fig. 2B), consistent with the higher sensitivity of the slugs' eyes to short-wavelength light (Suzuki et al, 1979;Matsuo et al, 2017Matsuo et al, , 2019. We judged the avoidance behaviour based on whether more than half of the slug's body was within the dark compartment (criterion number 1).…”
Section: Wavelength Dependency Of Avoidance Behavioursupporting
confidence: 54%
“…However, a larger percentage of animals was expected to avoid short-wavelength light if monochromatic light with an equivalent photon flux density was used instead. We and other groups also demonstrated that the eye of Limax is more responsive to short-wavelength blue light, especially when the eye is light adapted (Suzuki et al, 1979;Matsuo et al, 2017Matsuo et al, , 2019. The preferential use of short-wavelength light is thought to be a widely conserved phenomenon in the animal kingdom (Gehring and Rosbash, 2003;Erren et al, 2008), and the slugs also appear to have inherited this trait.…”
Section: ) Andsupporting
confidence: 53%
See 1 more Smart Citation
“…Electron microscopy was performed as described previously (Matsuo, Takatori, Hamada, Koyanagi, & Matsuo, ). Briefly, an isolated ST was fixed in 2% paraformaldehyde 2% glutaraldehyde in 20 mM phosphate buffer (pH 7.3) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Spectral sensitivity was measured by a modified method adopted from Suzuki et al (). The ERG was recorded from the surface of an isolated eye as described previously (Matsuo et al, ), except that the optic nerve was at the internal side of the recording electrode in order to record the spikes in the optic nerve fibers. The isolated eye was either kept in the dark (dark adaptation) or illuminated with 400‐nm light (11.2 μW/cm 2 , light adaptation) for 2 hr.…”
Section: Methodsmentioning
confidence: 99%